Elevated cerebrospinal fluid total tau in former professional athletes with multiple concussions. (4th June 2019) - Taghdiri, Foad; Multani, Namita; Tarazi, Apameh; Naeimi, Seyed Ali; Khodadadi, Mozghan; Esopenko, Carrie; Green, Robin; Colella, Brenda; Wennberg, Richard; Mikulis, David; Davis, Karen Deborah; Goswami, Ruma; et al.
Abstract : Objective: To identify CSF biomarkers that are related to decreased white matter (WM) integrity and poor cognitive performance in former professional athletes with a history of multiple concussions. Methods: Concentrations of phosphorylated tau181, total tau (t-tau), and β-amyloid in the CSF were measured in 3 groups: 22 former professional athletes with multiple concussions (mean ± SD age 55.9 ± 12.2 years), 5 healthy controls (age 57.4 ± 5.2 years), and 12 participants (age 60.0 ± 6.6 years) diagnosed with Alzheimer disease (AD). All participants in the former athletes group underwent diffusion tensor imaging to determine WM tract integrity and completed neuropsychological testing. We divided the former athletes group into those with normal (<300 pg/mL) and high (>300 pg/mL) CSF t-tau. Results: CSF t-tau in the former athletes group was significantly higher than in the healthy control group (349.3 ± 182.6 vs 188.8 ± 39.9 pg/mL, p = 0.003) and significantly lower than in the patients with AD (349.3 ± 182.6 vs 857.0 ± 449.3 pg/mL, p = 0.007). Fractional anisotropy values across all the tracts were significantly lower in the high CSF t-tau group compared to the normal CSF t-tau group ( p = 0.036). Participants in the high CSF t-tau group scored significantly lower on the Trail Making Test (TMT) Part B compared to the normal CSF t-tau group ( t scores 45.6 ± 18.8 vs 62.3 ± 10.1, p = 0.017). Conclusion: Our findings indicate that former athletes with multiple concussions are at increased risk of elevated levels of CSF t-tau and that high CSF t-tau is associated with reduced WM integrity and worse scores on the TMT Part B.